Inhibition of NF-κB prevents high glucose-induced proliferation and plasminogen activator inhibitor-1 expression in vascular smooth muscle cells - Jeong, In-Kyung (Korean Society for Biochemistry and Molecular Biology, 2011)
Recent epidemiologic studies clearly showed that early intensive glucose control has a legacy effect for preventing diabetic macrovascular complications. However, the cellular and molecular processes by which high glucose leads to macrovascular complications are poorly understood. Vascular smooth muscle cell (VSMC) dysfunction due to high glucose is a characteristic of diabetic vascular complications. Activation of nuclear factor-κB (NF-κB) may play a key role in the regulation of inflammation and proliferation of VSMCs. We examined whether VSMC proliferation and plasminogen activator inhibitor-1 (PAI-1) expression induced by high glucose were mediated by NF-κB activation. Also, we determined whether selective inhibition of NF-κB would inhibit proliferation and PAI-1 expression in VSMCs. VSMCs of the aorta of male SD rats were treated with various concentrations of glucose (5.6, 11.1, 16.7, and 22.2 mM) with or without an inhibitor of NF-κB or expression of a recombinant adenovirus vector encoding an IκB-α mutant (Ad-IκBαM). VSMC proliferation was examined using an MTT assay. PAI-1 expression was assayed by real-time PCR and PAI-1 protein in the media was measured by ELISA. NF-κB activation was determined by immunohistochemical staining, NF-κB reporter assay, and immunoblotting. We found that glucose stimulated VSMC proliferation and PAI-1 expression in a dose-dependent manner up to 22.2 mM. High glucose (22.2 mM) alone induced an increase in NF-κB activity. Treatment with inhibitors of NF-κB such as MG132, PDTC or expression of Ad-IκB-αM in VSMCs prevented VSMC proliferation and PAI-1 expression induced by high glucose. In conclusion, inhibition of NF-κB activity prevented high glucose-induced VSMC proliferation and PAI-1 expression.